# Calculate the average C-S bond energy

WatchPage 1 of 1

Go to first unread

Skip to page:

Report

#2

(Original post by

8) Use the following data to calculate the average C-S bond energy in CS2(l).

S(s) ---> S(g) Delta H? = 223 kJ mol-1

C(s) ---> C(g) Delta H? = 715 kJ mol-1

Enthalpy of formation of CS2(l) Delta H? = 88 kJ mol-1

CS2(l) ---> CS2(g) Delta H? = 27 kJ mol-1

How would you do this? I thought it is just 27 kJ mol-1 but clearly it is not

**adil12**)8) Use the following data to calculate the average C-S bond energy in CS2(l).

S(s) ---> S(g) Delta H? = 223 kJ mol-1

C(s) ---> C(g) Delta H? = 715 kJ mol-1

Enthalpy of formation of CS2(l) Delta H? = 88 kJ mol-1

CS2(l) ---> CS2(g) Delta H? = 27 kJ mol-1

How would you do this? I thought it is just 27 kJ mol-1 but clearly it is not

What is the definition of bond enthalpy?

Write out an equation to represent it and then construct this equation from the ones you are given.

0

reply

(Original post by

You must construct a Hess cycle, or manipulate the equations to give you the equation you require.

What is the definition of bond enthalpy?

Write out an equation to represent it and then construct this equation from the ones you are given.

**charco**)You must construct a Hess cycle, or manipulate the equations to give you the equation you require.

What is the definition of bond enthalpy?

Write out an equation to represent it and then construct this equation from the ones you are given.

0

reply

Report

#4

(Original post by

How can you construct a Hess cycle for this though? It would be C + S2 ---> CS2? And the elements at the bottom would be the same: C + S2? I am so confused...

**adil12**)How can you construct a Hess cycle for this though? It would be C + S2 ---> CS2? And the elements at the bottom would be the same: C + S2? I am so confused...

for example:

C(g) + 2S(g) -->CS

_{2}(g)

would represent the formation of two C-S bonds

0

reply

(Original post by

No, you must be more rigorous and take into account the states of matter...

for example:

C(g) + 2S(g) -->CS

would represent the formation of two C-S bonds

**charco**)No, you must be more rigorous and take into account the states of matter...

for example:

C(g) + 2S(g) -->CS

_{2}(g)would represent the formation of two C-S bonds

0

reply

Report

#6

(Original post by

But what after that?

**adil12**)But what after that?

What I'm saying is that you must construct your required equation using the equations given...

OK, so the equation you actually want is:

C(g) + 2S(g) --> CS

_{2}(g)

so construct it one step at a time from the other equations.

1. You want C(g). Is there any equation that uses it?

2. Then you want to add 2S(g). Is there any equation that contains S(g)? Well double it and add...

Until you eventually end up with the required equation (doing the same to all of the enthalpy changes)

0

reply

(Original post by

You can't read that post in isolation...

What I'm saying is that you must construct your required equation using the equations given...

OK, so the equation you actually want is:

C(g) + 2S(g) --> CS

so construct it one step at a time from the other equations.

1. You want C(g). Is there any equation that uses it?

2. Then you want to add 2S(g). Is there any equation that contains S(g)? Well double it and add...

Until you eventually end up with the required equation (doing the same to all of the enthalpy changes)

**charco**)You can't read that post in isolation...

What I'm saying is that you must construct your required equation using the equations given...

OK, so the equation you actually want is:

C(g) + 2S(g) --> CS

_{2}(g)so construct it one step at a time from the other equations.

1. You want C(g). Is there any equation that uses it?

2. Then you want to add 2S(g). Is there any equation that contains S(g)? Well double it and add...

Until you eventually end up with the required equation (doing the same to all of the enthalpy changes)

2) This one: S(s) --> S(g) (which is 223 kJ mol-1), so 223 x 2 = 446 kJ mol-1.

Then you add the 2?

0

reply

Report

#8

(Original post by

1) Right, and this equation uses it: C(s) --> C(g) (which is 715 kJ mol-1)

2) This one: S(s) --> S(g) (which is 223 kJ mol-1), so 223 x 2 = 446 kJ mol-1.

Then you add the 2?

**adil12**)1) Right, and this equation uses it: C(s) --> C(g) (which is 715 kJ mol-1)

2) This one: S(s) --> S(g) (which is 223 kJ mol-1), so 223 x 2 = 446 kJ mol-1.

Then you add the 2?

C(s) --> C(g)

S(s) --> S(g)

---------------

C(s) + S(s) --> C(g) + S(g)

is that what you want?

don't you want two sulphur particles?

why not multiply the sulphur equation by 2 and then add them?

But that will give you the reverse of what you want....

OK so reverse the equation and change the sign...

do you get the drift?

0

reply

(Original post by

If you add the two you get:

C(s) --> C(g)

S(s) --> S(g)

---------------

C(s) + S(s) --> C(g) + S(g)

is that what you want?

don't you want two sulphur particles?

why not multiply the sulphur equation by 2 and then add them?

But that will give you the reverse of what you want....

OK so reverse the equation and change the sign...

do you get the drift?

**charco**)If you add the two you get:

C(s) --> C(g)

S(s) --> S(g)

---------------

C(s) + S(s) --> C(g) + S(g)

is that what you want?

don't you want two sulphur particles?

why not multiply the sulphur equation by 2 and then add them?

But that will give you the reverse of what you want....

OK so reverse the equation and change the sign...

do you get the drift?

Anyways so you would then reverse the sign to get -1161, and then add 88 to get -1073, then divide by 2 to get -563.5 which is the answer? Still doesn't seem right because I didn't use the value of 27 kJ mol-1...

0

reply

Report

#10

(Original post by

Did I not say to x2 to the sulfur? It says in what I just wrote

Anyways so you would then reverse the sign to get -1161, and then add 88 to get -1073, then divide by 2 to get -563.5 which is the answer? Still doesn't seem right because I didn't use the value of 27 kJ mol-1...

**adil12**)Did I not say to x2 to the sulfur? It says in what I just wrote

Anyways so you would then reverse the sign to get -1161, and then add 88 to get -1073, then divide by 2 to get -563.5 which is the answer? Still doesn't seem right because I didn't use the value of 27 kJ mol-1...

_{2}(g) and for the enthalpy of formation you want CS

_{2}(l) as it is a liquid under standard conditions (and a very smelly one at that!)

So you must change the gas to a liquid using the value given...

0

reply

(Original post by

Because what you are making is CS

So you must change the gas to a liquid using the value given...

**charco**)Because what you are making is CS

_{2}(g) and for the enthalpy of formation you want CS_{2}(l) as it is a liquid under standard conditions (and a very smelly one at that!)So you must change the gas to a liquid using the value given...

0

reply

Report

#12

(Original post by

But how do you use that value given to convert gas to a liquid?

**adil12**)But how do you use that value given to convert gas to a liquid?

you are given:

CS

_{2}(l) ---> CS

_{2}(g) ΔHº = 27 kJ mol

^{-1}

So to reverse the process simply reverse the sign

CS

_{2}(g) ---> CS

_{2}(l) ΔHº = -27 kJ mol

^{-1}

0

reply

(Original post by

!!!!

you are given:

CS

So to reverse the process simply reverse the sign

CS

**charco**)!!!!

you are given:

CS

_{2}(l) ---> CS_{2}(g) ?Hº = 27 kJ mol^{-1}So to reverse the process simply reverse the sign

CS

_{2}(g) ---> CS_{2}(l) ?Hº = -27 kJ mol^{-1}
0

reply

Report

#14

(Original post by

So then wouldn't the answer be -1161 - 27 = -1188 kJ?

**adil12**)So then wouldn't the answer be -1161 - 27 = -1188 kJ?

_{2}(l).

S(s) ---> S(g) Delta H? = 223 kJ mol-1

C(s) ---> C(g) Delta H? = 715 kJ mol-1

Enthalpy of formation of CS2(l) Delta H? = 88 kJ mol-1

CS

_{2}(l) ---> CS

_{2}(g) Delta H? = 27 kJ mol-1

The average bond energy can be obtained by dividing the following equation by 2

CS

_{2}(g) --> C(g) + 2S(g)

So we must construct it stepwise.

-------------------------------------

equ1: C(s) ---> C(g) ΔH = 715 kJ mol

^{-1}

equ2: 2S(s) ---> 2S(g) ΔH = 446 kJ

--------------------------------------------------- add 1 + 2

equ3: C(s) + 2S(s) --> C(g) + 2S(g) ΔH = 1161 kJ

equ4: C(s) + 2S(s) --> CS

_{2}(l) ΔH = 88 kJ

-------------------------------------- --------- subtract 3 from 4

equ5: C(g) + 2S(g) --> CS

_{2}(l) ΔH = -1073 kJ

equ6: CS

_{2}(l) ---> CS

_{2}(g) ΔH = 27 kJ

-------------------------------------------------- add 5 + 6

C(g) + 2S(g) --> CS

_{2}(g) ΔH = -1046 kJ

Reverse and divide by 2 for C-S bond enthalpy =

__+523__kJ

0

reply

Report

#15

(Original post by

Use the following data to calculate the average C-S bond energy in CS

S(s) ---> S(g) Delta H? = 223 kJ mol-1

C(s) ---> C(g) Delta H? = 715 kJ mol-1

Enthalpy of formation of CS2(l) Delta H? = 88 kJ mol-1

CS

The average bond energy can be obtained by dividing the following equation by 2

CS

So we must construct it stepwise.

-------------------------------------

equ1: C(s) ---> C(g) ΔH = 715 kJ mol

equ2: 2S(s) ---> 2S(g) ΔH = 446 kJ

--------------------------------------------------- add 1 + 2

equ3: C(s) + 2S(s) --> C(g) + 2S(g) ΔH = 1161 kJ

equ4: C(s) + 2S(s) --> CS

-------------------------------------- --------- subtract 3 from 4

equ5: C(g) + 2S(g) --> CS

equ6: CS

-------------------------------------------------- add 5 + 6

C(g) + 2S(g) --> CS

Reverse and divide by 2 for C-S bond enthalpy =

**charco**)Use the following data to calculate the average C-S bond energy in CS

_{2}(l).S(s) ---> S(g) Delta H? = 223 kJ mol-1

C(s) ---> C(g) Delta H? = 715 kJ mol-1

Enthalpy of formation of CS2(l) Delta H? = 88 kJ mol-1

CS

_{2}(l) ---> CS_{2}(g) Delta H? = 27 kJ mol-1The average bond energy can be obtained by dividing the following equation by 2

CS

_{2}(g) --> C(g) + 2S(g)So we must construct it stepwise.

-------------------------------------

equ1: C(s) ---> C(g) ΔH = 715 kJ mol

^{-1}equ2: 2S(s) ---> 2S(g) ΔH = 446 kJ

--------------------------------------------------- add 1 + 2

equ3: C(s) + 2S(s) --> C(g) + 2S(g) ΔH = 1161 kJ

equ4: C(s) + 2S(s) --> CS

_{2}(l) ΔH = 88 kJ-------------------------------------- --------- subtract 3 from 4

equ5: C(g) + 2S(g) --> CS

_{2}(l) ΔH = -1073 kJequ6: CS

_{2}(l) ---> CS_{2}(g) ΔH = 27 kJ-------------------------------------------------- add 5 + 6

C(g) + 2S(g) --> CS

_{2}(g) ΔH = -1046 kJReverse and divide by 2 for C-S bond enthalpy =

__+523__kJ
0

reply

Report

#16

(Original post by

Hi, I get the rest of your work and did the same myself, however I dont understand why you have subtracted equation 3 from 4 could you please explain yourself thanks !!

**Hudl**)Hi, I get the rest of your work and did the same myself, however I dont understand why you have subtracted equation 3 from 4 could you please explain yourself thanks !!

so that is subsequently gets cancelled when added to equation 6

0

reply

Report

#17

(Original post by

To make sure that the carbon disulphide(l) appears on the RHS of equation 5 ...

so that is subsequently gets cancelled when added to equation 6

**charco**)To make sure that the carbon disulphide(l) appears on the RHS of equation 5 ...

so that is subsequently gets cancelled when added to equation 6

I kinda get you but its still not perfectly clear in my head

& why did you do equ 4 - 3 instead of equ 3 - equ 4 thanks in advance

0

reply

Report

#18

(Original post by

I kinda get you but its still not perfectly clear in my head

& why did you do equ 4 - 3 instead of equ 3 - equ 4 thanks in advance

**Hudl**)I kinda get you but its still not perfectly clear in my head

& why did you do equ 4 - 3 instead of equ 3 - equ 4 thanks in advance

0

reply

X

Page 1 of 1

Go to first unread

Skip to page:

### Quick Reply

Back

to top

to top